2022
DOI: 10.1371/journal.pntd.0010721
|View full text |Cite
|
Sign up to set email alerts
|

Helminth species dependent effects on Th1 and Th17 cytokines in active tuberculosis patients and healthy community controls

Abstract: Despite that the impact of different helminth species is not well explored, the current dogma states that helminths affect the Th1/Th2 balance which in turn affects the risk of tuberculosis (TB) reactivation and severity of disease. We investigated the influence of helminth species on cytokine profiles including IL-17A in TB patients and healthy community controls (CCs). In total, 104 newly diagnosed pulmonary TB patients and 70 HIV negative and QuantiFERON negative CCs in Gondar, Ethiopia were included follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The Th1/Th2 balance affects the outcomes of TB infection, CD4 + T cell cytokine expression pattern was associated with alterations in the systemic levels of Th1 and Th2 cytokines [ 26 ]. When mice were i.v or s.c immunized, splenic or inguinal LN mononuclear cells showed enhanced production of IL-6, IL-10, IFN-γ and TNF-α, while IL-17 only expressed highly in inguinal LN mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Th1/Th2 balance affects the outcomes of TB infection, CD4 + T cell cytokine expression pattern was associated with alterations in the systemic levels of Th1 and Th2 cytokines [ 26 ]. When mice were i.v or s.c immunized, splenic or inguinal LN mononuclear cells showed enhanced production of IL-6, IL-10, IFN-γ and TNF-α, while IL-17 only expressed highly in inguinal LN mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cytokines show an unambiguous picture of being either higher or lower in tuberculosis patients' plasma. Particularly, frequently studied candidate cytokines, such as TNF‐α or IFN‐γ, were elevated in the plasma of tuberculosis patients in several studies [20, 23–26, 29, 30, 32, 37, 44, 45, 47, 57, 60, 62, 68–71], but either or both did not differ in other studies [7–10, 14, 15, 18, 20, 21, 23–26, 29–32, 37, 40, 42, 44–47, 51–54, 57, 60–64, 68–71] (Figure 1b). Insufficient study cohort sizes and low statistical power in some studies likely contribute to heterogeneity, but this does not sufficiently explain differences.…”
Section: Heterogeneity Of Plasma Cytokine Expression In Pulmonary Tub...mentioning
confidence: 93%
“…However, to provide an overview of candidates, we screened studies based on a case/control design comparing ‘plasma’ or ‘serum’ samples from patients with pulmonary tuberculosis (before treatment) and matched controls. Sixty studies were identified that meet these criteria [7–66]. The selection criteria used for the definition of ‘controls’ varied between the studies, and this is at least partially due to a missing gold standard for the classification of ‘controls’ in human tuberculosis.…”
Section: Aberrant Plasma Cytokines In Tuberculosis Patients Reflect P...mentioning
confidence: 99%
“…There is a significant geographic overlap between TB and helminth infection, particularly in low and middle-income countries (LMICs), with 20–35% of people being co-infected [ 4 ]. The impact of helminths on cell-mediated immunity has been the subject of numerous investigations [ 5 , 6 , 7 , 8 , 9 ]. However, it is still unclear if parasite infection is associated with TB activation from a dormant condition to active disease development [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in some studies, helminths were demonstrated to have no impact on human tuberculin skin tests [ 19 ], Mtb infection [ 20 ], or the improvement of TB disease management [ 20 ]. Therefore, reports on TB immune responses in cases of helminth coinfection are variable and dependent on the infecting parasite and the type of study [ 8 , 9 , 21 ]. Studies involving Nippostrongylus brasiliensis (Nb) and mycobacterial coinfection in mice yielded divergent findings on Mtb growth control.…”
Section: Introductionmentioning
confidence: 99%